2021
DOI: 10.21093/sajie.v3i2.3354
|View full text |Cite
|
Sign up to set email alerts
|

Learning Model For Special Needs Children (ABK) in Inclusive Primary Schools

Abstract: The learning process of students with special needs requires a model that adapts to the specificity of students. Therefore, the learning of students with special needs must be formulated by choosing the right model, so that the delivery of subject matter is well understood. So that education for students with special needs is met the same as students in general. This research was conducted to determine the learning model of students with special needs inclusive elementary schools in Gresik district, namely SDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Skills improvement facilities, equipment owned by the school, and social facilities to practice students' skills directly with support from the education office are also very meaningful for the sustainability of life skills education in schools (observation, 2022). Because the education office has a role and responsibility for the development and progress of schools, in addition, parents are also one of the cornerstones of the successful implementation of life skills education; without the role of parents, students who attend special schools cannot develop well (Rahmawati et al, 2021).…”
Section: Support Factors and Inhibiting Factors Of Life Skills Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Skills improvement facilities, equipment owned by the school, and social facilities to practice students' skills directly with support from the education office are also very meaningful for the sustainability of life skills education in schools (observation, 2022). Because the education office has a role and responsibility for the development and progress of schools, in addition, parents are also one of the cornerstones of the successful implementation of life skills education; without the role of parents, students who attend special schools cannot develop well (Rahmawati et al, 2021).…”
Section: Support Factors and Inhibiting Factors Of Life Skills Educationmentioning
confidence: 99%
“…So that the learning objectives do not run optimally. Therefore, parents' opinions are very influential on the continuity of the implementation of Life Skills Education for SLB students (Rahmawati et al, 2021).…”
Section: Support Factors and Inhibiting Factors Of Life Skills Educationmentioning
confidence: 99%
“…These children often necessitate specialized therapy due to developmental anomalies, whether physical (e.g., blindness) or psychological (e.g., autism or ADHD) (Kusumawati, 2020;Rapin, 1991). Described as having unique qualities, children with special needs, or ABK, experience limitations and require assistance for daily tasks, therapy, education, and more (Rahmawati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This study found that training and professional development for teachers is very necessary to improve their skills and knowledge in dealing with special-needs children. Apart from that, research by Rahmawati et al (2021), examined the impact of learning models on the development of special-needs children in elementary schools. The results of this research show that the Special-Needs Children learning model that suits the specific needs of students with special needs in inclusive elementary schools can guarantee equal educational opportunities for all students.…”
Section: Introductionmentioning
confidence: 99%